How can the recall of early affiliative memories with peers influence on disordered eating behaviours? - Mendes, A. L. (2016)
The present study aimed to explore the role of early affiliative memories with peers on the adoption of disordered eating attitudes and behaviours through the mechanisms of external shame and self-judgment. The sample used in the current study comprised 632 women from the community, aged between 18 and 60 years old. The tested model explained 22% of eating psychopathology’s variance and showed excellent model fit indices. Results indicated that the impact of the recall of early positive memories with peers on eating psychopathology was fully carried through the mechanisms of external shame and self-judgment. In fact, these findings seem to suggest that the lack of warm and safe affiliative memories with peers is linked with higher levels of shame (e.g., feelings of inferiority and inadequacy), and also with higher vulnerability to engage in maladaptive emotional strategies (such as self-judgmental attitudes), which appears to explain the increase of disordered eating behaviours. These findings contribute to the understanding of the impact of peer-related early affiliative memories on the engagement in disordered eating. Furthermore, this study has significant clinical implications, emphasizing the importance of targeting shame and maladaptive emotional strategies, especially in a context involving early adverse emotional experiences with peers.